2020
DOI: 10.1590/0102-311x00041719
|View full text |Cite
|
Sign up to set email alerts
|

Do the determinants of self-rated health vary among older people with disability, chronic diseases or both conditions in urban Colombia?

Abstract: Our study aimed to identify the main determinants of self-rated health for individuals aged 60 years or older in Bogotá, Colombia, and if those determinants vary between groups. Data was obtained from the Demographic Health Survey 2011 for Bogotá. Logistic regression models were estimated to identify the determinants of excellent/good self-rated health among people aged 60 years or older living in Bogotá. Moreover, a subgroup analysis was conducted seeking to identify if the determinants changed between groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The reason behind dichotomising the outcome variable and using multivariate logistic regression was that this study focused on determinants of deteriorated SPH other than general SPH. A similar practice was noticed where the focus was on one aspect of SPH in previous studies [29][30][31][34][35][36][37]. For consideration of ordered regression logistic regression, the outcome variable was categorised into three groups: much worse or deteriorated (much worse and somewhat worse), neutral/about the same (about the same) and better/improved (somewhat better and much better).…”
Section: Methodsmentioning
confidence: 99%
“…The reason behind dichotomising the outcome variable and using multivariate logistic regression was that this study focused on determinants of deteriorated SPH other than general SPH. A similar practice was noticed where the focus was on one aspect of SPH in previous studies [29][30][31][34][35][36][37]. For consideration of ordered regression logistic regression, the outcome variable was categorised into three groups: much worse or deteriorated (much worse and somewhat worse), neutral/about the same (about the same) and better/improved (somewhat better and much better).…”
Section: Methodsmentioning
confidence: 99%
“…Through a nationally representative database, this study aims to quantify socioeconomic-related inequality in self-rated poor health for adults aged 50 or over in Brazil. The choice of self-rated health (SRH) due to the fact that several studies have shown that it is a good predictor of morbidity and mortality, even after controlling for several confounding factors [ 27 , 37 , 38 ], and that it can capture multiple health aspects of adults aged 60 years and over [ 39 ]. Even when looking at different cultural contexts, Pérez-Zepeda et al .…”
Section: Introductionmentioning
confidence: 99%